2016
DOI: 10.5688/ajpe80114
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Patient Encounters and Clinical Skills to Determine Competency in Ambulatory Care Advanced Pharmacy Practice Experiences

Abstract: Objective. To determine if the amount of exposure to patient encounters and clinical skills correlates to student clinical competency on ambulatory care advanced pharmacy practice experiences (APPEs). Design. Students in ambulatory care APPEs tracked the number of patients encountered by medical condition and the number of patient care skills performed. At the end of the APPE, preceptors evaluated students' competency for each medical condition and skill, referencing the Dreyfus model for skill acquisition. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Preceptors must make inherently subjective determinations of a student's competency based on past experiences. 5 These data show that over time, as predicted, trainees become more competent, as rated by both themselves and their preceptors. Additionally, these data show that despite differences in clinical sites and preceptors, trainees continue to progress professionally throughout residency.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Preceptors must make inherently subjective determinations of a student's competency based on past experiences. 5 These data show that over time, as predicted, trainees become more competent, as rated by both themselves and their preceptors. Additionally, these data show that despite differences in clinical sites and preceptors, trainees continue to progress professionally throughout residency.…”
Section: Discussionmentioning
confidence: 52%
“…Evaluating students’ competency as they proceed through residency is essential to the creation and evaluation of proper learning environments. Preceptors must make inherently subjective determinations of a student's competency based on past experiences . These data show that over time, as predicted, trainees become more competent, as rated by both themselves and their preceptors.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…These experiences are not sufficient to teach students to perform psychomotor skills competently, even for relatively straightforward patient problems. 26 Researchers in pharmacy education 27 found that students developed competency of clinical skills with more exposure to patient encounters or repeated skill performance. Interestingly, the educational content areas of psychosocial intervention and referral, acute care of injury/illness, and clinical examination and diagnosis were ranked as having more opportunities for real-time patient encounters.…”
Section: Opportunities For Real-time Patient Encounters In Clinical Pmentioning
confidence: 99%